Using python to analyze isometric force-time curves - Smith, J. C.; Nagatani, T.; Guppy, S. N.; Haff, G. G. (Strength and Conditioning Journal, 2025)
The isometric midthigh pull (IMTP) is a commonly used strength diagnostic tool that can give insight into an athlete's force-generating capacities. The resulting force-time curves generated are commonly analyzed using commercial software packages that provide a variety of metrics. Although these software packages are useful, they are often costly and operate as a "black box," limiting the control over how these metrics are calculated. A template created in Excel can be used to analyze isometric data. However, creating a custom script to analyze isometric trials can be more time-efficient. To provide users with an alternative analysis option, this article provides a guide for selecting IMTP force-time curves and variables for analysis and how to use Python to perform these analyses. Basic procedures are provided to ensure that accurate force-time curves are selected and analyzed, followed by strategies for using Python to read files, filter data, calculate force-time curve variables, graphically present data, and write results to a report are discussed. Although the script provided can be used to analyze the IMTP force-time curve data, it can be modified to examine other metrics as needed by the user (see, Supplemental Digital Content 1, https://links.lww.com/SCJ/A412).